Advances in organometallic chemistry. - Stone, F. Gordon A. (Francis Gordon Albert), 1925-; West, Robert, 1928- (Advances in organometallic chemistry, 1994)
This widely acclaimed serial contains authoritative reviews that address all aspects of organometallic chemistry, a field which has expanded enormously since the publication of Volume 1 in 1964. Almost all branchesof chemistry now interface with organometallic chemistry-the study of compounds containing carbon-metal bonds. Organometallic compounds range from species that are so reactive that they only have a transient existence at ambient temperatures to those thatare thermally very stable. They are used extensively in the synthesis of useful compounds on both small and large scales. Industrial processes involving plastics, polymers, electronic materials, and pharmaceuticals all depend on advances in organometallic chemistry. Key Features * In basic research, organometallics have contributed inter alia to: * Metal cluster chemistry * Surface chemistry * The stabilization of highly reactive species by metal coordination * Chiral synthesis * The formulation of multiple bonds between carbon and the other elements and between the elements themselves * Each volume of Advances in Organometallic Chemistry contains an index, and each chapter includes references.